Evaluating the satisfaction level of citizens in municipality services by using picture fuzzy VIKOR method: 2014-2019 period analysis - Yildirim, Bahadir Fatih; Kuzu Yıldırım, Sultan (Decision Making: Applications in Management and Engineering, 2022)
In this study, it is aimed to rank the satisfaction levels of the municipality services. For this purpose, 20 municipal services included in the Life Satisfaction Survey (LSS) that the Turkish Statistical Institution regularly applies every year are considered as alternatives. In addition, the satisfaction of citizens was evaluated not only for the last year, but also for the period of 2014-2019, and these years were considered as a set of criteria. LSS statistics contains the citizens’ responses which involve such opinion as abstain and refusal besides yes or no answers. For analyze the effect of all types of opinions on decision process, the participant responses constituting the dataset were converted into Picture Fuzzy Numbers (PFNs) consisting of 4 parameters (positive, neutral, negative, and refusal). Finally, we apply utilize VIKOR (VIseKriterijumska Optimizacija I Kompromisno Resenje) method by using PFNs arithmetic operators and evaluate the citizens’ satisfaction levels of the municipality services. As a result, it was determined that the municipal services with the highest satisfaction were graveyard (A18) and fire-fighting (A17) activities, while the services with the lowest satisfaction were zoning and city planning (A10) and control of food producing facilities (A20).